Comunicação, juventude e cidadania: consumo de redes sociais no contexto da Zona Leste de São Paulo - Mader, Renato Vercesi (2020)
The central objective of this thesis is to investigate whether the daily communication practices of young students, from the city of São Paulo, function as an evidence of a pubic media connection, based on the study of their media consumption on digital social spaces, such as the social networked sites Facebook, Twitter and Instagram. We are seeking to identify their perceptions and actions on citizenship in the daily context of the city's East Zone. In order to study these practices, the theoretical framework consists of: 1) The configuration of a networked society, with a high degree of communicational power through a digital mediating environment; 2) the post-massive media condition, in the process of mass-self communication; 3) the young subject, based on their social plurality; 4) the contemporary condition of citizenship in its different dimensions; and 5) The construction of citizenship senses and meanings, based on the subjects' daily communication practice, on social networks. The research universe consists of 26 subjects, all of whom are residents of the East Zone of São Paulo and students of the State Technical High School - ETEC - Martin Luther King unit, located in Vila Carrão, East Zone of São Paulo. The research methodology consists of: 1) online questionnaire, at ETEC; 2) semistructured individual interview; 3) non-participant observation in the school environment; and 4) Non-participant observation on digital social networks - Facebook, Instagram and Twitter - from 59 profiles belonging to the subjects, between October 2018 and June 2019. The theoretical path is based on the process of mass-self communication (CASTELLS, 2008), with a post-massive characteristic (GARCÍA CANCLINI, 2010) in digital social networks (BRIGNOL and COGO 2011), in which the young (BOURDIEU, 1984; FEIXA, 1998; and COGO, 2010) through daily media practice (COLDRY, LIVINGSTONE and MARKHAM, 2010) streamlines both their civic culture (DALHGREN, 2011), as well as their consumer culture (GARCÍA CANCLINI, 1997) establishing their perception of citizenship, from the possible dimensions (CORTINA, 1997; COGO, 2010; COGO, ELHAJJI and HUERTAS, 2012), as well as forms of mobilization and citizen action (DALHGREN, 2011; MOUFFE, 2015). The results of the research show how the consumption of social networks operates in the cultural and civic formation of young people from the post-massive media condition, especially through their interest in interactions around content linked to racial and gender relations and inequality Social. However, the study also reveals that the post-massive media condition of consumption circumscribes youth mobilizations and actions to social networks, making their exercise incipient in contexts that go beyond digital communication spaces.